Inhibiting Factors for E-Government Implementation in Local Government - Nia Karniawati (Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this research is to know inhibiting factor in e-government implementation in local government. This research was conducted in DPMPTSP West Java using qualitative descriptive methods. E-Government is the use of information and communication technology in the administration of government. The results of the study show that the success of e-government implementation is influenced by inhibiting factors in organizational change. These factors arise from internal and external the organization itself. The use of information technology in licensing services at DPMPTSP West Java through online licensing has been done since 2014. The results of the study show that people prefer to use licensing manually compared to online. This can be seen from the submission of recommendations for the use of KBU space. In 2015 only 11 of the 386 applicants used the online facility. In 2016 only 35 of the 528 applicants used the online facility. In 2017, none of the 551 applicants used the online facility (Karniawati: 2018). First, internal factor. The habit factor from within the DPMPTSP West Java institution is the habits that develop in the environment of the DPMPTSP West Java apparatus. These changes were made to improve service to the people. Effective leadership is needed to revitalize an organization and facilitate adaptation to a changing environment. Second, external factors. These are habits that develop in society. The community prefers to use the services of brokers in processing permits. The provision of online licensing facilities is an effort made by DPMPTSP West Java in eliminating the habit of using brokers. The goal of the online facility was to minimize the occurrence of direct physical contact between the applicant community and officers to avoid collusion. This is an effort to prevent the practice of corruption, collusion and nepotism.Keywords: inhibiting factors; e-government implementation; local government.